Progress in participation in tertiary education in India from 1983 to 2004 - Azam, Mehtabul 2001 (Policy research working paper, 2008)
"Using nationally representative household surveys, this paper examines the trends in attainment, enrollment, and access to tertiary (higher) education in India from 1983 to 2005. The findings suggest that there has been considerable progress in attainment and participation; however, they remain low. Important gaps exist in enrollment between rich and poor, rural and urban areas, men and women, disadvantaged groups and the general population, and states. Analysis of transition rates from secondary education to tertiary education and regression analysis indicate that inequality in tertiary education between disadvantaged groups and the general population is explained by low completion rates of secondary education. Inequality in tertiary education related to income, gender, rural residence, and between states is explained by: (i) differences in completion rates of secondary education, and (ii) differences in the probability of transitioning from secondary education to tertiary education. In particular, the importance of household income has grown markedly. Equitable expansion of secondary education is therefore critical for improving the equity of tertiary education. There is also a need to help qualified youth from low-income families and rural backgrounds to attend tertiary education, in particular the technical and engineering streams, in which participation is lower. "--World Bank web site